Peripheral blood smear – An expeditious test in the preliminary diagnosis of bone marrow embolism in a case of multiple fractures: A case report - Rajalakshmi B. Rajashekar; S Suchitha; Mahesh S Shetty; Apoorva P. Gowda (Indian Journal of Pathology and Microbiology)
Bone marrow embolism is known to occur after fractures of long bones such as the femur and pelvis. We report a case of multiple fractures in a 32-year-old female patient, demonstrating bone marrow elements in the peripheral blood as early as 2 hours after trauma. This is the first case being reported with an ante-mortem demonstration of circulating marrow emboli in the peripheral blood, while the previously reported cases have demonstrated the emboli in post-mortem examination. A careful correlation of the clinical history of trauma, hematology auto-analyzer results, and the presence of bone marrow particles and fat globules in peripheral blood helped in arriving at the diagnosis of fat embolism in our case irrefutably.